Saama Technologies : growth through a focused vertical market strategy - Sawhney, Mohanbir S.; Goodman, Pallavi (London : Kellogg School of Management, 2018)
After a successful transition from a projects-based IT business services company to a platform-driven analytics company, Saama's core leadership team gathered in 2017 to brainstorm the next phase of its growth. The year before, the team had decided to narrow its target market to the life sciences vertical. Saama now had to decide how to execute on this focused strategy by choosing a growth pathway within the life sciences vertical. Saama's leadership team was considering three alternatives: acquiring new customer accounts, developing existing customer accounts, or developing new products by harnessing artificial intelligence (AI) and blockchain technologies. The team had to evaluate these growth pathways in terms of both short-and long-term revenue potential, as well as their potential for sustaining Saama's competitive advantage.
Originally Published InSawhney, M., & Goodman, P. (2018). Saama Technologies: Growth through a focused vertical market strategy. 5-218-251. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Saama Technologies; Organizational change; Strategic planning; Information technology